1996
DOI: 10.1021/la9509514
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry and Patterning of Self-Assembled Monolayer Films Containing Aromatic Hydrocarbon Functional Groups

Abstract: The deep ultraviolet (λ < ∼250 nm) photochemistry of chemisorbed organosilane self-assembled films of the type R(CH2) n SiO−surface where n = 0, 1, 2 and R = phenyl, naphthyl, or anthracenyl is explored. Photochemistry is examined using 193 and 248 nm laser irradiation as well as deep ultraviolet lamp sources. It is demonstrated for a variety of systems, including single and multiple rings as well as heterocycles, that the primary photochemical mechanism is cleavage of the Si−C bond. Photocleavage of the organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
5

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 44 publications
8
61
5
Order By: Relevance
“…It has been well shown that the surface of the substrate can be modified by addition of a brush layer. 63 If the brush layer is made up of a homopolymer chemically similar to one of the blocks in a block copolymer, then that block of the copolymer will preferentially wet to the surface. If a random copolymer consisting of repeat units of the block copolymer with desirable compositions is coated to the substrate, the surface affinity can be controlled to be the same for each block, effectively neutralizing the surface.…”
Section: Chemical Templatingmentioning
confidence: 99%
“…It has been well shown that the surface of the substrate can be modified by addition of a brush layer. 63 If the brush layer is made up of a homopolymer chemically similar to one of the blocks in a block copolymer, then that block of the copolymer will preferentially wet to the surface. If a random copolymer consisting of repeat units of the block copolymer with desirable compositions is coated to the substrate, the surface affinity can be controlled to be the same for each block, effectively neutralizing the surface.…”
Section: Chemical Templatingmentioning
confidence: 99%
“…When the aromatic group is a simple phenyl ring or a fused aromatic ring system like naphthyl or anthracenyl, Si-C bond photocleavage predominates. [25,26] This mechanism is characterized by a uniform, monotonic decrease in the absorption spectrum of the SAM and release of the entire organofunctional group, detected as a single photoproduct by mass spectrometry, with increased exposure dose. At the same time, X-ray photoelectron spectroscopy (XPS) reveals that the Si2p band shifts to higher energy, consistent with formation of a free silanol at the surface.…”
Section: Photolysis Description and Photoproduct Identificationmentioning
confidence: 99%
“…For example, irradiation of the PES SAM leads to formation of volatile ethylbenzene, readily detected by its mass spectral signature, and free silanol groups on the substrate surface. [26] In contrast, for SAMs bearing benzyl halide chromophores, deep-UV irradiation leads first to scission of the benzyl carbonheteroatom bond. [10,25,31] The photolysis fragment containing the heteroatom is readily detected by mass spectrometry as it is released from the surface.…”
Section: Photolysis Description and Photoproduct Identificationmentioning
confidence: 99%
“…Hydrogen substituents on the silane (the "X" part) are most commonly methoxy groups (CH O), Cl, or a mixture of the two. The composition of the surface binding part strongly affects film ordering [52], the tendency of the film to grow multilayers [53], and, to a lesser extent, the packing density [54]. A thiol (RSH) forms highly ordered layers on surfaces of GaAs [55] or Au [56].…”
Section: A Sam'smentioning
confidence: 99%